A Means of Reducing Corruption: Greater Openness in Public Service Recruitment System - Jaehoon Kim; Hojun Lee (Korea Development Institute (KDI), 2014)
- Hiring former government officials can provide benefits in utilizing the accumulated knowledge, but also creates problems in that they can be abused as lobbying channels. - One of the primary causes of Korea's savings bank collapse was the hiring of former oversight agency officials and their prominent role in illegal lobbying. - The primary reason for the usage of former government employees as lobbying arms is to the close, personal ties between former and current officials, reinforced by the closed recruitment system. - The possibility exists that retired officials with close ties to current officials may be used as lobbying channels. - Closed recruitment practices were also implicated in a recent controversy over nuclear power plant corruption. - In order to weaken the close ties between current officials and former officials and to utilize the skills of private sector experts in the public sector, it is imperative to adopt a more advanced HR system, expand the open recruitment system, and increase the number of private sector experts across all departments. - Open recruitment was introduced in January 2000, with 20 percent of the total senior official positions selected from a pool of candidates from both inside and outside the government. However, questions have been raised about the system's effectiveness in terms of attracting experts from the private sector. - An advanced version of civil service HR system and improvements on the current state of partial application of the open recruitment and private sector expert recruitment is essential. This should be followed by large-scale expansion and application.
Keywords: 330